Extracellular vesicles in anti-tumor immunity. (November 2022) - Vergani, Elisabetta; Daveri, Elena; Vallacchi, Viviana; Bergamaschi, Laura; Lalli, Luca; Castelli, Chiara; Rodolfo, Monica; Rivoltini, Licia; Huber, Veronica
Abstract: To what extent extracellular vesicles (EVs) can impact anti-tumor immune responses has only started to get unraveled. Their nanometer dimensions, their growing number of subtypes together with the difficulties in defining their origin hamper their investigation. The existence of tumor cell lines facilitated advance in cancer EV understanding, while capturing information about phenotypes and functions of immune cell EVs in this context is more complex. The advent of immunotherapy with immune checkpoint inhibitors has further deepened the need to dissect the impact of EVs during immune activation and response, not least to contribute unraveling and preventing the generation of resistance occurring in the majority of patients. Here we discuss the factors that influence anddrive the immune response in cancer patients in the context of cancer therapeutics and the roles or possible functions that EVs can have in this scenario. With immune cell-derived EVs as leitmotiv, we will journey from EV discovery and subtypes through physiological and pathological functions, from similarities with tumor EVs to measures to revert detrimental consequences on immune responses to cancer.